2014
DOI: 10.1016/j.jaerosci.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol fast flow reactor for laboratory studies of new particle formation

Abstract: Understanding the fundamental mechanisms of new particle formation and growth (NPFG) is critical to the development of accurate quantitative models of atmospheric particulate matter. Challenges to elucidating the chemistry of these processes include accessing a variety of well-controlled experimental conditions approaching the point of new particle formation, and having an inexpensive system which can be reproducibly maintained with low levels of contaminants from previous runs and other sources. We describe h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 38 publications
(41 reference statements)
2
29
0
Order By: Relevance
“…During periods when the CS entering the OFR in ambient air was larger, it reduced the condensation of SOA onto new particles, consistent with the lower importance of this mode for an OFR study in the Los Angeles area . These results support the possibility of using flow reactors to study the potential for new particle formation and growth in different ambient air masses and sources (Ezell et al, 2014;Chen et al, 2015).…”
Section: Condensation Vs Nucleation In the Ofrsupporting
confidence: 74%
“…During periods when the CS entering the OFR in ambient air was larger, it reduced the condensation of SOA onto new particles, consistent with the lower importance of this mode for an OFR study in the Los Angeles area . These results support the possibility of using flow reactors to study the potential for new particle formation and growth in different ambient air masses and sources (Ezell et al, 2014;Chen et al, 2015).…”
Section: Condensation Vs Nucleation In the Ofrsupporting
confidence: 74%
“…The North Atlantic Aerosols and Marine Ecosystems Study NAAMES campaign has elucidated the contribution of NPF involving sulfur to CCN concentrations in the marine atmosphere (Sanchez et al, ). In addition to sulfuric acid, methanesulfonic acid (MSA) formed from oxidation of dimethyl sulfide (DMS) may contribute to NPF, as shown by CNT calculations (Kreidenweis et al, ), quantum chemical calculations (Bork et al, ; Wen et al, ), and flow tube experiments (Chen et al, ; Dawson et al, ; Ezell et al, ). Although MSA concentrations are comparable to sulfuric acid in the marine boundary layer, laboratory measurements showed that J of binary nucleation of MSA and water are relatively small (Wyslouzil et al, ).…”
Section: Npf Observations In Various Environmentsmentioning
confidence: 99%
“…Experiments were performed in a small volume (∼6.6 L) aerosol flow reactor ( Figure 1) similar in design to that described elsewhere. 80 The flow reactor has multiple inlets: three fixed rings upstream and three spokes, movable as a unit, downstream. Details of the flow reactor and determination of residence times are in Section 1 of the Supporting Information.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%